ENGANGING PIAUD STUDENTS IN ENGLISH SPEAKING THROUGH SONGWRITING PROJECTS - Uji Nur Hidayati (JETS, English Department of University of Uluwiyah Mojokerto, 2025)
Young learners acquire languages best through joyful, meaningful, and interactive experiences. Among various techniques in Teaching English to Young Learners (TEYL), the use of songs has proven to be one of the most effective for enhancing pronunciation, rhythm, and vocabulary. This study investigates how songwriting projects can enhance English-speaking proficiency and pedagogical readiness among PIAUD students (pre-service early childhood teachers) at IAI Uluwiyah Mojokerto. Employing a mixed-method design, the study involved 30 participants divided into an experimental group (songwriting-based speaking activities) and a control group (traditional speaking practice). Quantitative data were collected through pre- and post-speaking tests analyzed using paired and independent-sample t-tests, while qualitative data from interviews, reflective journals, and observations were analyzed using thematic analysis. The quantitative findings revealed significant improvement in the experimental group’s speaking scores (t = 12.54, p < .01, d = 1.28), particularly in fluency and pronunciation, indicating the strong impact of musical rhythm on oral performance. In conclusion, integrating songwriting projects into speaking classes effectively strengthens both linguistic competence and pedagogical creativity